Anarcho-Capitalism, Minarchism, and the Paradox of Deontology: Response to Wójtowicz - Dominiak, Łukasz; Wysocki, Igor (Roczniki Filozoficzne, 2025)
The present paper addresses a minarchist criticism of anarcho-capitalism based on the so-called paradox of deontology. The paper argues that minarchists are right in contending that minarchism does not run into a contradiction by recognizing individual rights and at the same time allowing their violations by the minimal state. However, the minarchist idea that the existence of the minimal state might be justified due to the paradox of deontology in which anarcho-capitalism is allegedly entangled is rejected. The whole discussion is conducted in the context of the exchange between Stanisław Wójtowicz’s rendition of the minarchist position as expressed in his recent paper “Libertarianism, Individual Rights, and the Paradox of Deontology: Rejoinder to Dominiak and Wysocki on Minarchism” (this issue) and Łukasz Dominiak and Igor Wysocki’s defense of anarcho-capitalism as presented in the target paper of Wójtowicz’s rejoinder, “The Anarcho-Capitalist Case against the State as a Challenge to the Minarchist Libertarians”, published also in Roczniki Filozoficzne recently.